Pengaruh Kepemimpinan dan Absensi Fingerprint terhadap Produktivitas Kerja Karyawan PT. KOMITRANDO GUNUNGKIDUL Dengan Disiplin Kerja sebagai Variabel Moderating - Fitri Nur Cahyani; Nur Rokhman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
This study aims to determine the effect of the fingerprint attendance model on the work productivity of PT. Komitrando Gunungkidul with work discipline as a moderating variable. This research was conducted in January 2021 at PT. Komitrando Gunungkidul. Data collection was carried out using a questionnaire. The population in this study were employees of PT Komitrando Gunungkidul. The sample in this research is only production employees (sewing) and those who have worked at least 6 months because what can be measured the work productivity is only employees in the sewing section. Thus the sample in this study was a sewing employee at PT. Komitrando Gunungkidul. Of the 100 existing permanent employees, only employees who have worked for at least 6 months, so the number of respondents taken is 60 sewing employees, and the collection uses the purposive sampling method, namely determining the sample with the consideration that employees whose productivity can be measured are only sewing. The results of this study indicate that partially, leadership has a negative effect on employee productivity, the application of the fingerprint absentee model affects employee performance, work discipline has a negative and significant effect on leadership and work productivity, work discipline has a positive and significant effect on the application of the fingerprint absence model and work productivity. employees.